Diagnostic Accuracy of Well’s Score in Clinically Suspected Deep Venous Thrombosis - Khafaji, Mawya A. (Journal of King Abdulaziz University: Medical Sciences, 2023)
The Wells scoring system for risk assessment of developing Deep Venous Thrombosis (DVT) is primarily designed to be used in the outpatient settings. We aimed to determine the validity, discrimination ability, and clinical utility of Wells scoring system in risk stratification of patients suspected of DVT in an inpatient setting in Saudi Arabia as compared to another outpatient population. All Patients who underwent lower limb Doppler ultrasound at King Abdulaziz University Hospital between January 2016 and July 2017 and were suspected to have DVT are included. A total of 1934 clinically-suspected DVT patients are analyzed (34.6% males and 65.4% females). 53.62% were outpatients and 31.8% were inpatients. Doppler ultrasound confirmed DVT in 304 patients. Incidence of DVT in outpatients was 5.9% for low probability; 8% for moderate probability; 18.5% for high probability, whereas the inpatients had an incidence of 4.1% for low probability; 8.4% for moderate probability; 15.7% for high probability. The negative predictive value of Wells score in outpatients is 94.1% and 95.9% for inpatients. Results of Well’s score demonstrate an excellent discrimination ability in ruling out DVT in both the outpatient and inpatient settings.